Diagnostic value of serum hyperbilirubinemia in acute appendicitis and its complications - Mir, Farooq A.; Aara, Shaugfta; Jan, Masrat; Wani, Nisar A. (International Surgery Journal, 2017)
Background: To increase diagnostic accuracy and to decrease complication rates secondary to acute appendicitis, a variety of different approaches have been described, including predictive scoring systems. To prevent the catastrophic effects of perforated appendix, a surgeon needs diagnostic tools which may signal perforation of appendix at earliest, as a result of which the delay in the management of perforated appendix will not be witnessed. Keeping in view the above facts, the diagnostic value of serum bilirubin in acute appendicitis and its complications has been evaluated. Methods: This prospective study was conducted on 100 patients who presented with clinical diagnosis of Acute Appendicitis. Role of serum bilirubin as a diagnostic tool in acute appendicitis and diagnostic value of hyperbilirubinemia as a predictive factor for appendiceal perforation was evaluated. . Estimation of serum bilirubin was done by Jendrassik and Gorf method using Hitachi – 912 automatic biochemistry analyzer. The sensitivity, specificity, positive predictive value, negative predictive value and accuracy of the investigations in the diagnosis of the acute appendicitis were calculated. Results: Serum bilirubin levels had a sensitivity of 84.1% and specificity of 83.3% in the diagnosis of acute appendicitis. The mean bilirubin level of patients with gangrenous appendicitis (2.1±1.2mg/dl) was significantly higher than the mean bilirubin level of patients with simple acute appendicitis (1.5 ±0.6) (p1=0.030 sig). A statistically significant difference was also observed in the mean bilirubin level of patients with perforated appendicitis (mean=2.9±1.6mg/dl) and mean bilirubin level of patients with simple acute appendicitis (p2=<0.0001 sig). However statistically non-significant difference was observed between the mean bilirubin level of patients with gangrenous and perforated appendicitis (p3=0.056 non- sig). Conclusions:Pre-operative assessment of serum bilirubin not only helps in acute appendicitis but also serves as a predictive factor for appendiceal perforation.